Diversity of Grasshopper in The Rice Fields of Kalijaga Village, East Lombok - Siti Nurul Inayah; Mohammad Liwa Ilhamdi; Didik Santoso (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Grasshoppers are the main herbivorous insects in the ecosystem, grasshoppers also act as pests, as predators, decomposers of organic matter and carrion eaters. To maintain the ecosystem of rice fields, grasshoppers have a very importants role in maintaining its stability. The research aimed to determine the level of diversity, evenness and dominance of grasshopper species in the rice fields of Kalijaga village. The kinds of this research was done by catching the grasshopper by using sweeping net. The location was taken in five location around Kalijaga such as west, east, north and middle location. The data was taken in nine times repeating for three month. The data was taken in the morning around 08.00-11.00 and afternoon 15.00-17.00 o’clock. The data analysis was used ecology index that include Shanon-Winner (H’), Evennes index (E’) and Simpson domination index (D). Based on data analysis was gotten that (1) there were 1,957 total of diversity index or include medium categories, (2) there were 0,816 the total number of grasshopper species of evenness index or include medium categories (3) there were 0,178 total number domination index of species with low categories.